Rapid modulation of synaptogenesis and spinogenesis by 17β-estradiol in primary cortical neurons - Sellers, Katherine J.; Erli, Filippo; Raval, Pooja; Watson, Iain A.; Chen, Ding; Srivastava, Deepak P. (Frontiers in Cellular Neuroscience, 2015)
In the mammalian forebrain, the majority of excitatory synapses occur on dendritic spines. Changes in the number of these structures is important for brain development, plasticity and the refinement of neuronal circuits. The formation of excitatory synapses involves the coordinated formation of dendritic spines and targeting of multi-protein complexes to nascent connections. Recent studies have demonstrated that the estrogen 17β-estradiol (E2) can rapidly increase the number of dendritic spines, an effect consistent with the ability of E2 to rapidly influence cognitive function. However, the molecular composition of E2-induced spines and whether these protrusions form synaptic connections has not been fully elucidated. Moreover, which estrogen receptor(s) (ER) mediate these spine-morphogenic responses are not clear. Here, we report that acute E2 treatment results in the recruitment of postsynaptic density protein 95 (PSD-95) to novel dendritic spines. In addition neuroligin 1 (Nlg-1) and the NMDA receptor subunit GluN1 are recruited to nascent synapses in cortical neurons. The presence of these synaptic proteins at nascent synapses suggests that the machinery to allow pre- and post-synapses to form connections are present in E2-induced spines. We further demonstrate that E2 treatment results in the rapid and transient activation of extracellular signal-regulated kinase 1/2 (ERK1/2), Akt and the mammalian target of rapamycin (mTOR) signaling pathways. However, only ERK1/2 and Akt are required for E2-mediated spinogenesis. Using synthetic receptor modulators, we further demonstrate that activation of the estrogen receptor beta (ERβ) but not alpha (ERα) mimics rapid E2-induced spinogenesis and synaptogenesis. Taken together these findings suggest that in primary cortical neurons, E2 signaling via ERβ, but not through ERα, is capable of remodeling neuronal circuits by increasing the number of excitatory synapses.